SARS-CoV-2 epidemiology, antibody dynamics, and neutralisation capacity in Irish healthcare workers in the era of booster COVID-19 vaccinations - McGrath, Jonathan; Kenny, Claire; Nielsen, Charlotte Salgaard; Domegan, Lisa; Walsh, Cathal; Rooney, Peadar; Walsh, Shane; Conlon, Niall; Brady, Gareth; Ibrahim, Aya; Dunne, Jean; McCormack, William; et al. (Frontiers in Medicine, 2023)
Background The PRECISE Study, a multi-phase cross-sectional seroprevalence study of anti-SARS-CoV-2 antibodies in Irish healthcare workers (HCW) investigated: (1) risk factors for SARS-CoV-2 seropositivity, (2) the durability of antibody responses in a highly vaccinated HCW cohort, and (3) the neutralisation capacity of detected antibodies, prior to booster COVID-19 vaccination. Materials and methods Serology samples were collected across two hospital sites in November 2021 and analysed using the Roche Elecsys Anti-SARS-CoV-2/Elecsys-S Anti-SARS-CoV-2 assays to detect anti-nucleocapsid (N) and anti-spike (S) antibodies respectively. Paired serology results from prior study phases were used to analyse changes in individual HCW serostatus over time. Risk-factors for SARS-CoV-2 infection were assessed for demographic and work-related factors. Antibody neutralisation capacity was assessed in a subset of samples via an in vitro ACE2 binding enzyme-linked immunosorbent assay. Results 2,344 HCW samples were analysed. Median age was 43 years (IQR 33–50) with 80.5% (n = 1,886) female participants. Irish (78.9%, n = 1,850) and Asian (12.3%, n = 288) were the most commonly reported ethnicities. Nursing/midwifery (39.3%, n = 922) was the most common job role. 97.7% of participants were fully vaccinated, with Pfizer (81.1%, n = 1,902) and AstraZeneca (16.1%, n = 377) the most common vaccines received. Seroprevalence for anti-SARS-CoV-2 antibodies indicating prior infection was 23.4%, of these 33.6% represented previously undiagnosed infections. All vaccinated participants demonstrated positive anti-S antibodies and in those with paired serology, no individual demonstrated loss of previously positive anti-S status below assay threshold for positivity. Interval loss of anti-N antibody positivity was demonstrated in 8.8% of previously positive participants with paired results. Risk factors for SARS-CoV-2 seropositivity suggestive of previous infection included age 18–29 years (aRR 1.50, 95% CI 1.19–1.90, p < 0.001), India as country of birth (aRR 1.35, 95% CI 1.01–1.73, p = 0.036), lower education level (aRR 1.35, 95% CI 1.11–1.66, p = 0.004) and HCA job role (aRR 2.12, 95% CI 1.51–2.95, p < 0.001). Antibody neutralisation varied significantly by anti-SARS-CoV-2 antibody status, with highest levels noted in those anti-N positive, in particular those with vaccination plus previous SARS-CoV-2 infection. Conclusion All vaccinated HCWs maintained anti-S positivity prior to COVID-19 booster vaccination, however anti-N positivity was more dynamic over time. Antibody neutralisation capacity was highest in participants with COVID-19 vaccination plus prior SARS-CoV-2 infection.